(untitled) (Journal of Computational Mathematics, 2022)
Preconditionings have proved to be a powerful technique for accelerating the rate of convergence of an iterative method. This paper, which is concerned with the conjugate gradient algorithm for large matrix computations, investigates an approximate polynomial preconditioning strategy. The method is particularly attractive for implementation on vector computers.